ChemInform Abstract: Designing and Synthesis of Novel Antimicrobial Heterocyclic Analogues of Fatty Acids. Issue 19 (13th May 2014) - Ahmad, Aiman; Ahmad, Anis; Varshney, Himani; Rauf, Abdul; Rehan, Mohd; Subbarao, Naidu; Khan, Asad U.
Abstract Isoxazole (III) and 4 dihydroisoxazoles of type (V) are prepared and tested for their antimicrobial activities.